Human well-being differs by community type: Toward reference points in a human well-being indicator useful for decision support. (September 2015) - Fulford, Richard S.; Smith, Lisa M.; Harwell, Mathew; Dantin, Darrin; Russell, Marc; Harvey, Jim
Graphical abstract: Highlights: Community classification system (CCS) was developed based on environmental dependencies. The CCS was used to compare human well-being among US coastal communities. Overall human well-being increased with population density and socio-economic diversity. Well-being differences are reference points for measuring change caused by decisions. Such reference points are important for using human well-being indices in decision making. Abstract: Human activity has growing impacts on the natural capital humans depend on for existence. While many of these impacts are regional, national, or international in scope, it is increasingly evident that decisions made at the local community level are also important. Yet, understanding the impacts of local decisions, as well as how to correct or mitigate these impacts, can be problematic, as communities differ in resources, priorities, dependencies on natural capital, and even opinions about whether these impacts actually affect quality of life. Every community has unique characteristics, however effective decision support at the community level requires common reference points in measures of human well-being upon which to base decision support. We have developed a community classification system that is intended to find such common ground in community characteristics and tie these common elements to measures of human well-being. This community classification system was developed in the USA with publically available data on resource dependence, socio-economic composition, and existence of natural capital. The resulting classification was applied to coastal communities at the county level and then used to predict human well-being based on an existing human well-being index. Coastal communities were separated into eight characteristics groups based on Bayesian cluster analysis. Classification groups were found to be associated with significant differences in human well-being. More importantly, significant differences in specific elements of well-being were associated with key community characteristics, such as population density and economic dependence on local natural resources. In particular, social cohesion and the leisure time were strong elements of well-being in low density communities with high natural resource dependence but this association weakened as population densities and economically diversity increased. These sorts of commonalities in community type that can be tied to differences in human well-being are important because they provide clear ties to environmental service flows, as well as a meaningful reference point from which to measure the local impacts of decisions as changes in community-specific human well-being.